A new species of Microhyla (Anura: Microhylidae) from the Malay Peninsula - Das, I.; Norsham, Yaakob; Sukumaran, J. (Centre for Herpetology, Madras Crocodile Bank Trust, 2007)
A new species of microhylid of the genus. Microhyla is described from the Malay Peninsula.M.mantheyi new species, was formerly assigned to M.bornensis, and has been earlier reported from southern Thailand, Peninsular Malaysia and Singapore.